Amino acids and fatty acids in patients with beta thalassemia major - Koca, Tugba; Canatan, Duran; Örmeci, Ahmet Rifat; Koca, Yavuz Savas; Duman, Handan; Baykal, Aslı; Akcam, Mustafa (Acta Biomedica Atenei Parmensis, 2020)
Background: Oxidative damage and increasing of lipid peroxidation are caused by chronic iron overload in patients with beta thalassemia major. Fatty acids are important structural elements for palmitoylation of membrane proteins which constitute a great part of natural membranes. Oxidative damages caused by reactive oxygen derives in thalassemic erythrocytes can be determined with lipid peroxidation, protein oxidation, and antioxidant system elements. The aim of study was to evaluate the relationship between amino acid and fatty acid levels with iron overload and antioxidant enzymes in beta thalassemia major. Methods: A total 40 patients with beta thalassemia major with regular blood transfusion and chelating agents were included in the study. The levels of serum amino acid, fatty acid, ferritin, antioxidant enzymes and malondialdehyde were measured. Results: Only C16- palmitoyl level was found significantly low in patients, other fatty acids and amino acids were in normal range. There were lower malondialdehyde and ferritin levels in patients with low C-16 palmitoyl level (p<0.05). Conclusions: The high levels of ferritin and malondialdehyde in the patients with low C16-palmitoyl levels might be caused by this fatty acid’s preventative effect on oxidative stress.